1969
DOI: 10.1021/ic50078a021
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dimethylaminodifluorophosphine, (CH3)2NPF2

Abstract: Dimethylaminodifluorophosphine, (CH3)zNPFz (mp -W0), crystallizes with four formula units in an orthorhombic cell with a = 10.808 (12) A, b = 7.601 ( 7 ) A, and c = 6.259 (6) b a t -110'. A total of 458 photographically recorded and visually evaluated X-ray data were used to determine the structure, which has been refined to R = 0.069. A space group ambiguity was resolved in favor of Pnma following least-squares refinement in both Pnma and PnZia and consideration of the effect of a slight scaling error in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

1970
1970
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 2 publications
1
33
1
Order By: Relevance
“…These data clearly suggest a p~---d,~ interaction between the N lone-pair electrons and the P atom. Similar bond distances have been observed in the compounds (CH3)~NPF2 (Morris & Nordman, 1969), P-N = 1.628 (5) A, and NHEPF 2 (Brittain, Smith, Lee, Cohn & Schwendeman, 1971) whose microwave determination gave P--N = 1.650 (4) A. The P-N bond distances determined in this study are longer than that reported for (CH3)ENPFEB4H8 (La Prade & Nordman, 1969), P--N = 1.585 (6) A.…”
Section: Introductionsupporting
confidence: 86%
“…These data clearly suggest a p~---d,~ interaction between the N lone-pair electrons and the P atom. Similar bond distances have been observed in the compounds (CH3)~NPF2 (Morris & Nordman, 1969), P-N = 1.628 (5) A, and NHEPF 2 (Brittain, Smith, Lee, Cohn & Schwendeman, 1971) whose microwave determination gave P--N = 1.650 (4) A. The P-N bond distances determined in this study are longer than that reported for (CH3)ENPFEB4H8 (La Prade & Nordman, 1969), P--N = 1.585 (6) A.…”
Section: Introductionsupporting
confidence: 86%
“…Such planarity is common in amino-phosphorus compounds in which an acyclic amino group is in ct position to a three- (Morris & Nordman, 1969;Brittain, Smith, Lee, Cohn & Schwendeman, 1971;Forti, Damiani & Favero, 1973) or four-coordinate (Camerman & Camerman, 1973; The plane of the C-N bonds bisects the S(1)-P-S(3) angle and N-C(9) eclipses the P=S double bond. This stereochemistry around the P--N bond seems to be quite general in three-and four-coordinated P compounds and can explain the equatorial orientation of the P-N bond.…”
Section: Discussionmentioning
confidence: 99%
“…were studied by 1 H, 13 C, 15 N, 29 Si, and 31 29 Si) were determined. Low temperature NMR spectra were measured for derivatives for which rotation about the P N bond at room temperature is fast, showing the presence of two rotamers at low temperature.…”
Section: R = Bz R = Ph (16) R = R = Ph (17) R = R = Me 3 Si (18))mentioning
confidence: 99%
“…Low temperature NMR spectra were measured for derivatives for which rotation about the P N bond at room temperature is fast, showing the presence of two rotamers at low temperature. The respective conformation of these rotamers could be assigned by 13 C, 15 N, and 31 P NMR spectroscopy. Isotope-induced chemical shifts 1 15/14 N( 31 P) were determined for all compounds at natural abundance of 15 N by using Hahn-echo extended polarization transfer experiments.…”
Section: R = Bz R = Ph (16) R = R = Ph (17) R = R = Me 3 Si (18))mentioning
confidence: 99%